Peningkatan Kapasitas Jalan Kabupaten Dan Evaluasi Kelayakan Ruang Manfaat Jalan - Ahmad Fuad Mustafid; Abd. Rahim Nurdin; Tamrin Mallawangeng (Program Studi Teknik Sipil Universitas Bosowa, 2023)
Road capacity is the ability of a road segment to accommodate the ideal traffic flow or volume within a certain time unit, expressed in the number of vehicles that pass a certain road section in one hour (vehicles/hour), or by considering the various types of vehicles passing through a road, the unit is used. The capacity uses units of passenger cars per hour or (pcu) / hour. The road being analyzed is the Jatie – Bua road along the 25 km in Tellulimpoe sub-district, Sinjai district. The purpose of this study was to determine the capacity of the Jatie – Bua road and have the space belonging to the Jatie road segment according to existing road standards, the analysis was carried out using the 1997 road capacity manual method. Based on the analysis and discussion, the road capacity of the Jatie – Bua segment was stored as follows C = 1373.9 pcu/hour. The results of the study, it was also found that several permanent buildings and n semi-permanent above the road shoulder, side channel, and safety threshold which is part of the space belonging to the road. The suggestion that can be taken is that the current road capacity is not able to serve for the next few years, so it is necessary to widen the road according to standards with road shoulder adjustments to further improve user safety and comfort.